Mucocele in Pediatric: A case report - Putri Gusti Hakiki; Siti Rusdiana Puspa Dewi (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2023)
Introduction: Mucocele is a lesion on the oral mucosa as a benign mass caused by retention or extravasation of mucus in the tissue around the lamina propria. Mucocele mainly occurs on the lower lip mucosa. Purpose: This case report aimed to describe the history, clinical examination, and simple surgical removal of mucocele, thus it can strengthen the knowledge of the general dental practitioner. Case presentation: A 6-year-old female child visited the Dental and Oral Hospital of South Sumatera Province with complaints of swelling on the right inner lower lip about 2 weeks ago. The swelling disappeared because it ruptured due to being bitten 2 months ago, then reappeared in the last 2 weeks. Her mother also said that her child had unconsciously bit her lower lip almost every day for the last few months. The results of an objective examination of the lesion showed a fluctuating vesicle lesion on the labial mucosa of the right lower lip, approximately 5 mm in diameter, did not bleed easily, was soft and painless upon palpation, had a translucent bluish-pink color. Based on the results of subjective, objective, and supporting examinations, the diagnosis in this case was a mucocele with a differential diagnosis of fibroma and hemangioma. The treatment plan included surgical excision and post-surgery instructions as well as instructions to stop the bad habits to prevent the recurrences. Conclusion: Mucocele is one of the most common soft tissue lesions in children and it can be treated with simple surgical excision.